Joint Cost in the Packing Industry - Putnam, George E. (Journal of Political Economy, 1921)
The Report' of the Federal Trade Commission on the "Profits of the Packers" should receive the most careful attention of economists and accountants who are interested in the problem of joint cost. In unmistakable language the commission condemns as unsound the methods of cost calculation employed in the packing industry, albeit the methods are fundamentally those which are followed by the United States Department of Agriculture and the various public-service commissions in dealing with similar cost problems. The economist will note that the commission offers no constructive or practical suggestions as to how the problem of cost-finding in the by-product industries should be solved; and the keen accountant who is not led astray by the sentiment that the word of a government body is the last word will realize that the "generally recognized principles of accounting," which the packers are openly accused of ignoring, are principles which have been evolved to meet the needs of business enterprises essentially different in character from the business of meat-packing concerns. Before reviewing in detail the criticisms offered by the Federal Trade Commission, it may be well to note those peculiarities of the packing industry which have given rise to the present system of cost accounting. In the first place, the meat-packer does not assemble raw materials into a finished unit as is the case in most manufacturing industries. He is engaged in dividing his raw material, consisting of a single commodity, into a great many finished products, differing widely from one another both in character and utility. Obviously, there is no way of ascertaining the money cost of each of the various products. Another peculiarity about the packing industry which affects the accounting system is its complexity. From the point of view of functions performed, the industry is a collection of four fairly distinct industries, each performing a different function. These